Cell autonomous and noncell‐autonomous role of NF‐κB p50 in astrocyte‐mediated fate specification of adult neural progenitor cells. Issue 1 (19th October 2016) - Cvijetic, Suzana; Bortolotto, Valeria; Manfredi, Marcello; Ranzato, Elia; Marengo, Emilio; Salem, Rita; Canonico, Pier Luigi; Grilli, Mariagrazia
Abstract : In previous work, we demonstrated that NF‐κB p50 acts as crucial regulator of adult hippocampal neural progenitor cells (ahNPC). Indeed, NF‐κB p50 knockout (KO) mice are characterized by remarkably reduced hippocampal neurogenesis. As a follow up to that work, herein we show that when cultured in vitro, ahNPC from wild type (WT) and p50KO mice are not significantly different in their neurogenic potential. This observation prompted us to investigate cell‐autonomous and noncell‐autonomous consequences of p50 absence on neuronal fate specification of ahNPC. In particular, we focused our attention on astrocytes, known to provide soluble proneurogenic signals, and investigated the influence of WT and p50KO astrocyte conditioned media (ACM) on WT and p50KO ahNPC differentiation. Interestingly, while WT ACM promoted both neuronal and astroglial differentiations, p50KO ACM only supported astroglial differentiation of WT ahNPC. By using a LC–MS/MS approach, we identified some proteins, which are significantly upregulated in p50KO compared with WT astrocytes. Among them, lipocalin‐2 (LCN‐2) was recognized as a novel astroglial‐derived signal regulating neuronal fate specification of ahNPC. Interestingly, LCN‐2 proneurogenic effect was greatly reduced in p50KO NPC, where LCN‐2 receptor gene expression appeared downregulated. In addition to that, we demonstrated p50KO NPC unresponsiveness to both neuronal and astroglial fate specification signals from WT and p50KO ACM, and we identified a reduced expression of α2δ1, a thrombospondin‐1 receptor, as another phenotypic change occurring in ahNPC in the absence of p50. Altogether, our data suggest that dysregulated NPC‐astrocyte communication may contribute to a reduced hippocampal neurogenesis in p50KO mice in vivo . GLIA 2016 GLIA 2017;65:169–181 MAIN POINTS: NF‐κB p50 absence in astrocytes reduces the proneurogenic effects of their soluble signals on ahNPC. p50 absence in ahNPC impairs their responsiveness to astrocyte‐derived signals. Lipocalin‐2 is a novel astrocyte‐derived proneurogenic molecule.